Complementary absorbing ternary blend containing structural isomeric donor polymers for improving the performance of PC61BM-based indoor photovoltaics. (14th April 2021) - Chau, Hong Diem; Kwon, Na Yeon; Park, Su Hong; Hwang, Jinhyo; Kataria, Meenal; Harit, Amit Kumar; Woo, Han Young; Cho, Min Ju; Choi, Dong Hoon
Abstract: In this study, two structural isomeric polymers, TTE36 and TTE25, were synthesized and their photophysical properties and photovoltaic device performance were investigated. Because of the different linking positions of carboxylate in their thienothiophene unit, these polymers can be classified as two isomers and exhibit significantly different properties. A mixture of these two polymers was effectively applied as the donor for a highly reliable active layer in organic indoor photovoltaics (IPVs) because of its good miscibility, and especially, of its broad complementary absorption which overlapped the emission spectrum of the white light-emitting diode lamp. The ternary IPV system, achieved by mixing the wide-bandgap TTE25 polymer with the medium-bandgap TTE36 polymer, followed by blending with [6, 6]-phenyl-C61-butyric acid methyl ester (PC61 BM), exhibited significantly enhanced open circuit voltage and short circuit current density, thus improving the power conversion efficiency (PCE) of the IPV system. Compared to the TTE36 :PC61 BM-binary-blend-based IPV system, the TTE36 :TTE25 :PC61 BM (0.8:0.2:1.0 wt ratio)-ternary-blend-based IPV system exhibited an increase in PCE from 6.81% to 11.15% under 1000 lux white LED light illumination. These results indicate that the addition of TTE25 to the TTE36 :PC61 BM binary blend improves the morphology and light-harvesting properties of the active layer. Graphical abstract: The ternary active layer using two structural isomeric donor polymers is an effective strategy for enhancing the efficiency of IPVs. Image 1 Highlights: Two structural isomeric polymers, TTE36 and TTE25, were synthesized successfully. They showed different absorption and PL properties. Their blend improves the film morphology and light-harvesting properties of the active layer. The PCE (11.15%) of TTE36:TTE25-based IPVs is higher than that of TTE36-based IPVs.